Pengaruh Literasi Keuangan dan Dukungan Pemerintah Terhadap Keberlanjutan UMKM: Analisis Mediasi Orientasi Pemasaran - Endang Kristiawati; Mustaruddin; Nur Afifah (Journal of Trends Economics and Accounting Research, 2024)
The contribution of MSMEs to economic development and job creation in Indonesia cannot be underestimated. As the times accelerate, progress in the economic field is getting higher, and competition is getting tighter, the business world today needs to take strategic steps to continue to grow and compete. This study aims to examine the mediating effect of marketing orientation variables on the influence of financial literacy and government support on the sustainability of MSMEs. The method used in this research is descriptive quantitative. The data collection techniques used were observation, documentation and questionnaires. The data analysis and processing technique is Median Regression with the help of the SPSS test tool and the Sobel test. The population and samples in this study were MSMEs in West Kalimantan. The results of this study indicate that marketing orientation is able to mediate the effect of financial literacy on the sustainability of MSMEs. Furthermore, marketing orientation is not able to mediate the effect of government support on the sustainability of MSMEs.